Facile preparation of hybrid molybdenum dioxide/NiMn2O4 nanocomposites with two substrate matrixes for the assisted photo-degradation, oxygen evolution reaction and antimicrobial performances - Zairov, Rustem R.; Syed, Asad; Elgorban, Abdallah M.; Subramaniam, Manjula; Wong, Ling Shing; Janani, Baadal Jushi; Sinyashin, Oleg G. (Colloids and surfaces. A, Physicochemical and engineering aspects, 2025)
In this work, the synthesis of MoO2/NiMn2O4 has been conducted via a hydrothermal method and decorated on the two substrate matrixes including reduced graphene oxide, and poly-5-amino-1,4-naphthoquinone. The prepared nanocomposites were characterized by various techniques. Also, the prepared nanocomposites were applied to electrochemical, photo-degradation, and antimicrobial activities. The results showed that MoO2/NiMn2O4/RGO (MNMOR) have excellent performance in the oxygen evolution reaction (OER), due to the greatest active surface area. In addition, the photocatalytic degradation analysis was conducted on removal of Acetaminophen (ACE), displaying response of 98.85 %, within 100 min with followed the pseudo-first-order model as kinetically behavior. The optimum conditions are ACE concentration:20 mg/L, catalyst amount: 0.02 g/L, pH: 7, for ACE degradation. The antibacterial performance was evaluated versus gram-positive and negative bacterial strains, displaying highly activity. These results pave a way for manufacturing innovation in future. [Display omitted]